Forms of Modernity : Don Quixote and Modern Theories of the Novel - Schmidt, Rachel Lynn (Book collections on Project MUSE., 2011)
"It's a critical cliche that Cervantes' Don Quixote is the first modern novel, but this distinction raises two fundamental questions. First, how does one define a novel? And second, what is the relationship between this genre and understandings of modernity? In Forms of Modernity, Rachel Schmidt examines how seminal theorists and philosophers have wrestled with the status of Cervantes' masterpiece as an 'exemplary novel', in turn contributing to the emergence of key concepts within genre theory.